ANALISIS TINGKAT PENGETAHUAN TENTANG DETEKSI DINI KANKER PAYUDARA DENGAN PERILAKU PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA REMAJA PUTRI - Dewi Indriani; Ambar Dwi Retnoningrum (JURNAL SABHANGA, 2023)
Introduction : Breast cancer is a type of cancer with the highest percentage of new cases (Kemenkes RI, 2016). Secondary prevention with early detection behavior, is considered the most rational effort to reduce mortality from breast cancer (RI Ministry of Health, 2015). The purpose of this study was to analyze the level of knowledge about early detection of breast cancer by breast self-examination behaviour in female adolescents in Sukorejo, Rejoso District, Nganjuk District. Method : The design of this research was analytic survey with cross sectional design. Simple random sampling technique. The sample in SukorejoVillage is 89 teenage girls. Data collection tool uses a questionnaire.